Penjualan on-line berbasis media sosial dalam perspektif ekonomi Islam - Al-Arif, M. Nur Riyanto (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
Contemporary transactions along with the development of existing technologies have given rise to other forms of trading i.e. on-line trading. This paper aims to look at how the Islamic economic perspectives associated with on-line trading. The method used in this paper was library research. On-line trading had fulfilled the shariah principle, i.e. al-aqid, si>ghah, al-maâqu>d alaih and the goal of the transaction. The transaction models that can be adopt in trading on line are bayâ al-mura>bahah and bayâ al-sala>m. Trading online had several advantage for buyer and seller, but trading on-line also had several problems. So, we must to had a strategy to minimize the various problems that may arise.